Alloying of poly(vinyl chloride) to reduce plasticizer migration - Noreen Thomas (2004)
Concern over the migration of low molecular weight plasticiser from flexible PVC used in toys and medical products has lead to the commercialisation of a number of plasticising polymers. In this study the plasticising behaviour of an ethylene/vinyl acetate/carbon monoxide terpolymer (Elvaloy® from Du Pont) was investigated. Blends of PVC, Elvaloy 742 and Di-octyl phthalate (DOP) were processed on a twin-roll mill and compression moulded into plaques. These materials were characterised in terms of their hardness, Tg, clarity, mechanical properties and plasticiser migration behaviour. The ratios of PVC/DOP/Elvaloy investigated were determined by experimental design. Using this approach it was possible to model the results and produce contour plots to map out the properties of a wide range of formulations. It was confirmed that Elvaloy 742 is compatible with PVC and has a plasticising effect: this was demonstrated both in terms of a reduction in Shore A hardness and a reduction in Tg. Plasticiser migration was reduced in proportion to the amount of liquid plasticiser replaced. Plasticising with Elvaloy gave an improvement in tear strength. However, at constant hardness there was no improvement in tensile strength from replacing DOP with Elvaloy.